Determination of Ascorbic Acid (Vitamin C) by Direct Injection Enthalpimetry (DIE) Technique The ascorbic acid content of juices of some fruits and pharmaceutical tablets of Vitamin C was determined by a homemade apparatus of DIE technique using a thermoc - Abdullah, A. M. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The ascorbic acid content of juices of some fruits and pharmaceutical tablets of Vitamin C was determined by a homemade apparatus of DIE technique using a thermocouple as heat sensor. The method is simple, speed, low cost and the different types of turbid, colored samples can be analyzed without any problem. The results were of a valuable accuracy and precision, and the recovery of results was with acceptable values